On some first-order differential subordination - Nunokawa, M.; Sokół, J.; Cho, N.E.; Owa, S.; YAVUZ, EMEL (My University, 2014)
Let denote the class of functions f that are analytic in the unit disc and normalized by f(0) = f′(0) − 1 = 0. In this paper, we investigate the class of functions such that in . We determine conditions for α and β under which the function f is univalent, close-to-convex, and convex. To obtain this, we first estimate ∣Arg{f′(z)}∣ which improves the earlier results.
Keywords: Close-to-convex functions; Convex functions; Starlike functions; Subordination